Pengaruh Kalsinasi Hidrotalsit Terhadap Aktivitas Katalitik Pada Reaksi Transesterifikasi Etil Asetat Menjadi Metil Asetat - Januar, Imam (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2014)
This research is aim to study the optimum of time and calcination ffict on hydrotalcite in transesterification reaction in obtaining metyl ester. The reagen has been used in this reaclion were etyl acetat, methanol and hydrotalcite as catalyst. In the reaction was used various of times; 0,5, 1, 2, 3 hours and various catalysts; calcinated catalyst and non-calcinated catalyst. The caracterization of hydrotalcite has used XRD, BET and FTIR instrument.The result of GC intrepetation showed the decreasing of methanol concentration. The result caracterization hydrotalcite using XRD showed difractogram d= 7,60882; 3,79933 and 8,42876…. These peaks have similiarity to the d of Mg/Al standar of hydrocalcite. BET intrepetation showed the specific surface area is 12,337 m2/g, averages of pores are 15,352 …, volume of pores is 3,9 x 10-2 cm3/g. The result of FTIR showed the appearance of hydroxil group with the wavelength; 3450,40 cm-1 and 1635,38 cm-1, CO32- was 1366,66 cm-1  and 660,20 cm-1, MgO was 553,23 cm-1, Zn-O is 447,04 cm-1, these wavelengths showed the characteristic of hydrocalcite. Infrared intrepretation showed that the compound Mg-Zn-AlCO3.4H2O was hydrocalcite